Integrating Contextual Problem-Based Animated Videos in Mathematics Learning: A Strategy to Improve Students' Understanding of Fractions - Divayani, Made Pertiwi; Agustika, Gusti Ngurah Sastra; Chindytia (Universitas Pendidikan Ganesha, 2024)
Mathematics learning, particularly in the topic of fractions, often presents challenges for fourth-grade students due to its abstract nature and the lack of engaging instructional media. Therefore, this study aims to develop contextual problem-based animated video media to enhance students' understanding of fraction concepts and improve their learning motivation. The research employed the ADDIE development model. Data collection was conducted through questionnaires and tests. The questionnaires were used to gather feedback from experts and students, while the tests were designed to assess students' achievement in understanding fractions. Prior to use, the research instruments were piloted to ensure their validity and reliability. Validity was tested using the point-biserial correlation formula, whereas reliability was measured using the Kuder-Richardson 20 (KR-20) formula. Additionally, the difficulty level and discriminative power of test items were analyzed. The collected data were analyzed using quantitative descriptive analysis, qualitative descriptive analysis, and inferential statistical analysis (t-test). A normality test using the Shapiro-Wilk formula was conducted before the t-test to ensure the data followed a normal distribution. The findings indicate that the developed media met the criteria for feasibility and effectiveness in enhancing students’ learning outcomes. The use of contextual problem-based animated videos has proven to be an engaging and interactive alternative in mathematics instruction.